Acellular Cauda Equina Allograft as Main Material Combined with Biodegradable Chitin Conduit for Regeneration of Long‐Distance Sciatic Nerve Defect in Rats. Issue 17 (25th July 2018) - Sun, Xun; Wang, Yu; Guo, Zhiyuan; Xiao, Bo; Sun, Zhen; Yin, Heyong; Meng, Haoye; Sui, Xiang; Zhao, Qing; Guo, Quanyi; Wang, Aiyuan; Xu, Wenjing; et al.
Abstract: Autologous nerve grafting (ANG), the gold standard treatment for peripheral nerve defects, still has many restrictions. In this study, the acellular cauda equina allograft (ACEA), which consists of biodegradable chitin conduit and acellular cauda equina, is developed. The cauda equina is able to complete decellularization more quickly and efficiently than sciatic nerves under the same conditions, and it is able to reserve more basal lamina tube. In vitro, ACEA shows superior guidance capacity for the regeneration of axons and migration of Schwann cells compared to acellular sciatic nerve allograft (ASNA) in dorsal root ganglion culture. In vivo, ACEA is used to bridge 15 mm long‐distance defects in rat sciatic nerves. On day 21 after transplantation, the regenerative distance of neurofilaments in the grafting segment is not significantly different between the ACEA and ANG groups. At week 12, ACEA group shows better sciatic nerve repair than chitin conduit only and ASNA groups, and the effect is similar to that in the ANG group as determined by gait analysis, neural electrophysiological, and histological analyses. The above results suggest that the ACEA has the potential to become a new biological material as a replacement for autografting in the treatment of long‐distance nerve defects. Abstract : Acellular cauda equina allograft (ACEA) consists of chitin conduit and acellular cauda equina. In vitro, ACEA shows superior guidance capacity for the regeneration of axons and migration of Schwann cells. In vivo, ACEA shows superior effect for repairing long‐distance defects of sciatic nerve. It has the potential to become a new biological material in the treatment of long‐distance nerve defects.